Pyrazolopyridines II: Synthesis and Antibacterial Screening of 6-Aryl-3-methyl-1-phenyl-1H-pyrazolo[3,4-b]pyridine-4-carboxylic Acids - Maqbool, Tahir; Nazeer, Areesha; Naeem Khan, Muhammad; C. Elliott, Mark; Ain Khan, Misbahul; Ashraf, Muhammad; Nasrullah, Muhammad; Arshad, Shafia; Ali Munawar, Munawar (Asian Journal of Chemistry, 2014)
5-Amino-3-methyl-1-phenyl-1H-pyrazole was prepared to react with various aromatic aldehydes and pyruvic acid to afford 6-aryl-3-methyl-1-phenyl-1H-pyrazolo[3,4-b]pyridine-4-carbxylic acids. The prepared compounds were characterized by Mass, IR, 1H, 13C NMR spectra and CHN analysis data. Various 6-aryl-3-methyl-1-phenyl-1H-pyrazolo[3,4-b]pyridine-4-carbxylic acids synthesized during this work were also evaluated for their antibacterial activities. Some of these compounds were found to be good antibacterial agents.